INVENTORY MANAGEMENT FOR OPERATIONAL EFFICIENCY AND EFFECTIVENESS OF COMPANY: a case study - Belisario, Douglas Jhonata; Rodolpho, Daniela (Revista Interface Tecnológica, 2022)
The internal movement of materials and parts within an organization deserves special care and must be fully engaged with the planning and control of production to meet its needs quantitatively, qualitatively and at the right time. In view of this, an accuracy in the inventory system is necessary to support and accurately guarantee the information and the effectiveness of this flow, which is continuous. As they are interconnected, purchasing activities can also suffer distortions with divergences in inventories and, as a result, an increase in the cost of materials and/or services and deficiencies in their planning. The objective of this study was to demonstrate that the improvement or reduction in possible errors in the counting of items in stock, in the monthly inventory closings of the warehouse and in the production line helps the company to remain competitive. The company under study is characterized as a medium-sized company in the rubber products sector, inserted in the automotive chain. A bibliographic research was used to support the importance of production management and materials control. A survey was also used with employees and managers of the sectors involved in the processes, who responded to specific questionnaires. Among the results obtained, it was possible to note that there are flaws in the control of materials that can be corrected and Reverse Logistics was also presented as a solution for the destination given to the scrap of parts accounted for by the company.
Keywords: Materials Management; Inventory